Interior topology: a new approach in topology - Amer Himza Almyaly (International Journal of Advances in Applied Sciences, 2022)
This paper defined a new type of topology known as Interior topology. This work falls among the types of topology (such as general topology, supra topology, generalized topology, and filter) that are motivated by real-world concepts such as the orbits of planets around the sun, electron orbits around the nucleus, and so on. This form of topology is self-contained. The primary objective of this study is to respond to the question “Is general topology capable of producing Interior topology?”. Finally, we define the base for Interior topology which is called i-base.